2015
DOI: 10.1016/j.neuroscience.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Region-specific role for GluN2B-containing NMDA receptors in injury to Purkinje cells and CA1 neurons following global cerebral ischemia

Abstract: Motor deficits are present in cardiac arrest survivors and injury to cerebellar Purkinje cells (PCs) likely contribute to impairments in motor coordination and post-hypoxic myoclonus. NMDA receptor mediated excitotoxicity is a well-established mechanism of cell death in several brain regions, but the role of NMDA receptors in PC injury remains understudied. Emerging data in cortical and hippocampal neurons indicates that the GluN2A-containing NMDA receptors signal to improve cell survival and GluN2B-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Some differences in survival and ischemic time were observed in TRPM2 KO mice (Table 1). CA/CPR resulted in delayed neuronal cell death in the CA1 region of the hippocampus, as previously described (Kofler et al, 2004; Allen et al, 2011; Quillinan et al, 2015). We tested the ability of the Sirt2 inhibitor AGK to protect neurons against cerebral ischemia.…”
Section: Resultssupporting
confidence: 58%
“…Some differences in survival and ischemic time were observed in TRPM2 KO mice (Table 1). CA/CPR resulted in delayed neuronal cell death in the CA1 region of the hippocampus, as previously described (Kofler et al, 2004; Allen et al, 2011; Quillinan et al, 2015). We tested the ability of the Sirt2 inhibitor AGK to protect neurons against cerebral ischemia.…”
Section: Resultssupporting
confidence: 58%
“…In addition, PSD-93 can bind to NR2A and nNOS and facilitate ischemic brain injury [16,31] . On the other hand, neuronal excitatory toxicity interacted with microglia-induced inflammatory response in ischemic brain injury [32][33] . After ischemic stroke, neurons activate microglia through a variety of neurotransmitters or regulators such as glutamate, fractalkine (FKN, CX3CL1), and NO.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, excitatory amino acid toxicity of neurons interacts with microglial-induced inflammatory responses in cerebral ischemia-reperfusion injury [17,18] . After ischemic stroke, neurons activate microglia through a variety of regulatory factors, and the activation of NMDAR is closely related to the activation of microglia [3] .…”
Section: Introductionmentioning
confidence: 94%
“…This pattern of TIGAR expression was correlated with the sensitivity of neurons to ischemia/reperfusion insult. [28][29][30][31] . For example, many studies have reported that the expression of NMDA receptor subunits changes during neuronal development [28,32] .…”
Section: Discussionmentioning
confidence: 99%